Extended-spectrum beta-lactamase and carbapenemase-producing Gram-negative bacteria in urinary tract infections in Ethiopia: a systematic review and meta-analysis - Mitkie Tigabie; Getnet Ayalew; Lidetu Demoze; Kebebe Tadesse; Yalewayker Gashaw; Muluneh Assefa (BMC Urology)
Abstract Background Urinary tract infection (UTI) is one of the most common infections worldwide, particularly in developing countries. It also is among the most prevalent nosocomial infections, largely due to the widespread use of urinary catheters in hospitalized patients. These catheters often act as reservoirs for multidrug-resistant bacteria, including extended-spectrum beta-lactamase- and carbapenemase-producing pathogens, which significantly limit treatment options and delay appropriate care. This systematic review and meta-analysis, therefore, aimed to assess the pooled prevalence of ESBL- and carbapenemase-producing Gram-negative bacteria associated with UTIs in Ethiopia. Methods A systematic literature search of all available electronic databases such as PubMed, Hinari, Google Scholar and EMBASE, Scopus, and African journal online was performed. The quality of the included studies was assessed via the Joanna Briggs Institute critical appraisal tool. The data were extracted from the eligible studies via Microsoft Excel 2019 and analysed via STATA version 17. The presence of between-study heterogeneity was checked via the Cochrane Q statistic, and the magnitude was quantitatively measured via I2 statistics. To determine the possible sources of heterogeneity, a subgroup analysis was performed. Additionally, a sensitivity analysis was conducted to determine the influence of single studies on the pooled estimates. Publication bias was checked via funnel plots and Egger’s regression tests. A p value of less than 0.05 was evidence of heterogeneity and small study effects according to the Cochrane Q statistic and Egger’s test, respectively. The protocol was registered (PROSPERO ID: CRD42024564656). Results A total of 20 studies with 1010 and 557 Gram-negative bacterial isolates from 6263 and 2199 study participants for extended-spectrum beta-lactamase and carbapenemase, respectively, were included. The overall pooled prevalence rates of extended-spectrum beta-lactamase-producing and carbapenemase-producing Gram-negative bacteria in Ethiopia were 30.92% (95% CI: 21.23–40.61, P < 0.001) and 15.12% (95% CI: -0.28–30.52, P < 0.001), respectively. The most common extended-spectrum beta-lactamase producers were Klebsiella spp., 43.91% (95% CI: 30.63–57.18, P < 0.001), followed by E. coli, 31.14% (95% CI: 21.27–41.01, P < 0.001). Similarly, the predominant carbapenemase producer was Klebsiella spp., 17.78% and E. coli, 11.42%. Conclusion and recommendations. In this meta-analysis, the pooled prevalence of extended-spectrum beta-lactamase- and carbapenemase-producing Gram-negative bacteria was significantly high. During the development of empiric treatment protocols for urinary tract infections, extended-spectrum beta-lactamase- and carbapenemase-producing uro-pathogens should not be underestimated.